PENGARUH PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP PENURUNAN SKALA NYERI DISMENOREA - Sutrisno - -; Vitri Dyah Herawati; Wa Ode Adilla Putri Muna (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2022)
Dysmenorrhea is a gynecological complaint due to an imbalance of the hormone progesterone in the blood, resulting in pain that most often occurs in women. One of the herbal products that are commonly consumed in the community is a sour turmeric drink. The content of sour turmeric can inhibit the occurrence of cyclooxygenase reactions so that it can inhibit and reduce inflammation and will reduce and inhibit uterine contractions that cause dysmenorrhea. The purpose of the study was to determine the effect of giving sour turmeric drink to decrease the pain scale of dysmenorrhea in adolescent girls. The type of research is pre-experiment using a one group pretest and posttest design. The sample of this study were 52 female adolescent respondents who experienced dysmenorrhea with purposive sampling technique. Data analysis was carried out by using univariate test and bivariate paired sample t-test. The measuring instrument used in this study was the VDS pain scale and the SOP for giving sour turmeric drink. The results showed that most of the young women during the study before consuming sour turmeric drinks regularly, experienced severe pain as much as 69.20%, moderate pain as much as 30.80%, After consuming sour turmeric drinks regularly there was a decrease in the pain scale, namely a mild scale and moderate as much as 50%. The results of the statistical test paired sample t-test obtained a value of 0.001 < 0.05, meaning that the turmeric drink has a significant effect on reducing pain. Keywords: Dysmenorrhea, sour turmeric drink, pain